Asian business groups : context, governance and performance - Carney, Michael (Chandos Asian studies series., 2008)
The Asian economic landscape is dominated by various types of business group. Asian Business Groups provides a comprehensive review and introduction to the different types of business group. The origins and founding context of groups from particular national settings form the basic structure of the book. Emphasis is given to both the similarities and differences in group governance and performance and the implications for Asian international competitiveness are addressed. Multidisciplinary framework that integrates managerial, sociological, and economic perspectives on business groups and permits analysis of both their positive and negative aspectsComprehensive survey of empirical findings on the financial and market performanceSensitivity to the changing historical context and major events that have shaped business group development and dynamics.